Assessing the Oral-Health-Related Quality of Life in Patients with Dental Prosthetics: A Cross-Sectional Study from Eastern Croatia - Ingrid Kovačević; Ivana Barać; Katarina Major Poljak; Slavko Čandrlić; Marija Čandrlić (Oral)
Objectives: This cross-sectional study aimed to evaluate the oral-health-related quality of life (OHRQoL) among patients with fixed, removable, and combined dental prosthetic restorations in Osijek, Croatia, focusing on potential variations by gender, age, and prosthetic type. Methods: This study included 313 patients treated at dental clinics within the Osijek-Baranja County Health Center. The standardized Oral Health Impact Profile-14 (OHIP-14) questionnaire, validated in Croatian (OHIP-CRO14), was used to assess the participants’ OHRQoL. Statistical analyses were conducted to explore associations between demographic factors, prosthetic types, and OHRQoL domains. Results: Psychological discomfort emerged as the domain with the lowest reported OHRQoL, whereas social disability was the least affected. Gender showed no significant association with OHRQoL outcomes. However, age influenced OHRQoL scores. Patients with fixed prosthetic restorations reported better OHRQoL in functional limitation, physical pain, and physical disability compared to those with removable or combined prosthetics. Conclusions: Patients with fixed prosthetic restorations reported better OHRQoL, particularly in functional limitation, physical pain, and physical disability domains. While no significant gender differences were observed, age significantly influenced physical disability scores, with younger participants reporting lower scores and older participants higher scores. These results emphasize the importance of prosthetic type in improving OHRQoL and guiding clinical decision-making in dental practice.